Global prevalence of preeclampsia, eclampsia, and HELLP syndrome: a systematic review and meta-analysis - Vera-Ponce, Víctor Juan; Loayza-Castro, Joan A.; Ballena-Caicedo, Jhosmer; Valladolid-Sandoval, Lupita Ana Maria; Zuzunaga-Montoya, Fiorella E.; Gutierrez De Carrillo, Carmen Inés (Frontiers in Reproductive Health, 2025)
IntroductionHypertensive disorders of pregnancy represent a leading cause of maternal and perinatal morbidity and mortality worldwide. However, prevalence estimates of preeclampsia, eclampsia, and HELLP syndrome vary considerably across studies and regions.ObjectiveTo determine the global prevalence of preeclampsia, eclampsia, and HELLP (Hemolysis, Elevated Liver enzymes, and Low Platelet count) syndrome, analyze their geographical distribution, and evaluate temporal and methodological trends.MethodologyA systematic review with meta-analysis was conducted. SCOPUS, Web of Science, PubMed, and EMBASE databases were searched through May 2025. Observational studies reporting prevalence data using standardized diagnostic criteria were included. Prevalences were pooled using a random-effects model with Freeman-Tukey double arcsine transformation. Subgroup analyses by diagnostic criteria and countries and meta-regressions by publication year and sample size were performed.ResultsSeventy studies on preeclampsia (2,465,570 participants), 21 on eclampsia (9,782,257 participants), and nine on HELLP syndrome (133,611 participants) were analyzed. The global prevalence of preeclampsia was 4.43 (95% CI: 3.73–5.20), with significant differences between ACOG (4.68%) and ISSHP (3.66%) criteria. For eclampsia, the prevalence was 0.43% (95% CI: 0.19%–0.76%), while the estimate for HELLP syndrome is 0.39% (95% CI: 0.16%–0.72%), which must be interpreted with considerable caution as it is derived from a limited pool of only nine studies. Marked regional disparities were identified, with higher prevalences in low-income countries. Meta-regression for preeclampsia revealed a non-significant increasing trend over time (p = 0.23) and a significant inverse correlation with sample size (p < 0.01). For eclampsia, neither the temporal trend (p = 0.68) nor the association with sample size (p = 0.65) was statistically significant.ConclusionsHypertensive disorders of pregnancy affect 4.43% (95% CI: 3.73%–5.20%) of pregnancies globally for preeclampsia, 0.43% (95% CI: 0.19%–0.76%) for eclampsia, and 0.39% (95% CI: 0.16%–0.72%) for HELLP syndrome, with considerable variations according to regions and diagnostic criteria. The upward trend underscores the need to strengthen epidemiological surveillance systems and preventive programs, especially in high-prevalence areas.